Social Welfare Issues for Women in Urban Areas: A Systematic Review of Indonesian Literature - Bayu Anshor Mursalin; Bella Satiyo Putri; Joice Amelia (Women, Education, and Social Welfare, 2024)
This study systematically reviews social welfare challenges faced by urban women in Indonesia and proposes policy recommendations to address gender-based disparities. Using a Systematic Literature Review (SLR) approach, five peer-reviewed articles published between 2020 and 2024 were analyzed. Findings reveal persistent structural and socio-economic inequalities, including limited access to education, employment, healthcare, and social protection. Vulnerable groups such as domestic workers, single mothers, and women at risk of socio-economic vulnerability (WRSE) remain marginalized despite existing welfare programs. Cultural norms, patriarchal values, and inconsistent implementation of gender-responsive policies exacerbate these challenges, especially in rapidly urbanizing areas. This review underscores the urgent need for inclusive, gender-sensitive, and participatory welfare strategies that strengthen women’s economic empowerment, improve access to social services, and enhance resilience against crises. By synthesizing contemporary evidence, this study provides insights for policymakers, educators, and stakeholders to develop equitable and sustainable urban welfare systems that foster gender equality and social justice.